Implementation of Educational Marketing Strategy in Attracting Interest of New Students at Darul Hijrah Putri Hidayatullah Islamic Boarding School Sidoarjo - Bayu Prasetio; Nur Fazria Masfufah; Choirunisa Karina; Rita Ambarwati Sukmono (Formosa Journal of Sustainable Research, 2023)
This research aims to explain and determine the obstacles faced in marketing strategies, and provide recommendations for marketing strategies that must be carried out for future improvements that must be carried out by the Darul Hijrah Putri Hidayatullah Sidoarjo Islamic boarding school. The approach used in this research is a qualitative descriptive approach. The subjects used as respondents for this research were informants such as the head of the Islamic boarding school, the public relations team, and teachers. This research was conducted at the Darul Hijrah Putri Hidayatullah Sidoarjo Islamic boarding school, which is precisely located in Perum. Kahuripan Nirwana, Block BA IX No. 15-16, Sidoarjo. The data collection techniques used in this research are observation, interviews, documentation. The results of this research are that the marketing strategy at this cottage is promotion. The recommendation for this Islamic boarding school is to determine the name of the Islamic boarding school and there is no need to change the name if it is not too urgent. Establish strong policies. Carry out good marketing management, which is planned, systematic and measurable. Preparing a special team to carry out marketing strategies so that this team will be able to implement it more optimally